Tuturan tindakan komunikatif subjek diri dalam wacana narasi - Suwignyo, Heri (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
Placing self-autonomy of human beings as purely rational subjects represents one extreme, while positioning rational human subjects as entirely dependent on psychological and socio-economic relations represents the other extreme. This study aims to explain how the main character, Minke, in narrative discourse addresses these two extremes. The data in this research were in the form of textual units analyzed using Bühler’s semiotic model. The results of the study show that there are three ways used by subjects to express themselves: (1) the symptomic way, expressed through validity claims of honesty; (2) the signalic way, shown through regulative speech using normative validity of accuracy; and (3) the symbolic way, realized through objective validity claims of truth. The findings imply that the subject’s orientation in performing communicative speech acts is the achievement of self-understanding and rational agreement without violence.